ANGKA BANDING NETROFIL/LIMFOSIT DI POPULASI DEWASA MUDA - Arie Yanti; Uleng Bahrun; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2016)
Previous studies have shown that neutrophil/lymphocyte ratio in bacteremia is higher than nonbacteremia, therefore it could beused as a marker to distinguish both conditions in patients with sepsis .Another study on oncology patients in ICU showed a correlationbetween the severity of clinical course and the increase of neutrophil/lymphocyte ratio. In physiological condition, neutrophil/lymphocyteratio <5, while in pathological conditions (severe infection or systemic inflammation) neutrophil/lymphocyte ratio increases >6.Neutrophil/lymphocyte ratio is a sensitive, fast, cost effective and applicable laboratory test for routine use, therefore this test result canbe used as the parameter to assess clinical condition of patients. However, a reference value of neutrophil/lymphocyte ratio has neverbeen defined, especially in Makassar City, South Sulawesi Province. The aim of this study was to know the neutrophil/lymphocyte ratioin a healthy young adult population. A cross sectional study was conducted from March to April 2014, involving residents (specialisticcandidates in Medical Faculty, Hasanuddin University, who underwwent medical checkup and voluntarily joined this study. Samplesconsisted of 198 persons who fulfilled the inclusion criteria with an age range between 24-40 years old, comprising 84 males (42.42%)and 114 females (57.58%). The neutrophil/lymphocyte ratio for all samples was 1.95 (1.15-4.74). Mann Whitney test showed thatthere was no significant difference of neutrophil/lymphocyte ratio between males and females, 1.88 (1.25-4.74) vs 1.95 (1.15-4.12),p=0.65 and neither between the age group 21-30 years old and 31-40 years old, 1.95 (1.21-4.74) vs 1.94 (1.15-4.09), p=0.82.